Arrangement of Green Open Space on River Borders with Constructed Wetlands Concept - Saputra, Stepanus Andi; Sudarwani, Margareta Maria; Eni, Sri Pare (Universitas Negeri Semarang, 2022)
Abstract. The decline in river quality is due to the role of 60%-70% of domestic waste, 30% of industrial waste, and 10% of agricultural and livestock waste that pollutes rivers. In addition, because there are settlements on the banks of the river, if it is not handled, the quality of the rivers in Jakarta will certainly be bad. One way of treating wastewater is Constructed Wetlands, the goal is to improve water quality and reduce the harmful effects of waste, as well as water conservation efforts. Constructed Wetlands are usually applied to settlements that have yards, while settlements in Jakarta currently only have narrow yards there are no yards left. From this aspect, the post-normalization riverbank arrangement will be carried out using the Constructed Wetlands approach. The research located at the Kampung Baru, Cakung,River, East of Jakarta. To find out the results of this application, the method used is descriptive in knowing the conditions of settlements, and then data collection will be carried out from literature reviews and interviews. Furthermore, an analysis is carried out with basic mathematical calculations to answer the space requirements in the application of Constructed Wetlands so that it will produce a spatial pattern model for settlements.